Testing and performance of immobilized Fenton photoreactions via membranes, mats and modified copolymers. (2003) - Fernandez, J.; Nadtochenko, V.; Enea, O.; Bozzi, A.; Yuranova, T.; Kiwi, J.
Abstract : During the last 6 years our laboratory has developed Fenton immobilized catalysts for the partial or total destruction of toxic organic compounds and their mixtures. This paper reports on Fe-supported noncorrosive supported membranes and fabrics like: Nafion, Nafion-glass mats and polyethylene block copolymers. These novel supported catalysts have shown acceptable kinetic rates, resistance to the leaching ofFe 3+ into the solution and no corrosion to the highly oxidative radicals generated in the solution during Fenton immobilized photo-assisted catalysis. Nafion-Fe membranes degrade Orange II under visible light only up to pH 4.8. In the case of nafion glass mats supportedFe 3+ -ions, the initial pH could be raised up to 8 or above. The pH decreased to about 4 during the photodegradation of Orange II due to the formation of intermediate carboxylic acids but the costly initial acidification process necessary in the case of homogeneous Fenton processes is avoided. Carboxylates and carboxylic acids were observed by IR spectroscopy on the surface of the supported catalysts towards the end of the photodegradation process as well as carboxylic acids detected by HPLC. The IR bands are found at 1523 and 1557cm -1 in the case of the copolymer-Fe 3+ corresponding to two types of iron-carboxylate species. The formation of carboxylates explains the drop of pH during the photodegradation to values between 3 and 4 corresponding to thepK a of the carboxylic functional group.